Cyclic voltammetry study on the reduction of nitrate and nitrite on a copper electrod - Thinh, Nguyen Viet; Phuong Thoa, Nguyen Thi; Hung, Le Quoc (Vietnam Journal of Chemistry, 2014)
The cathodic reduction of nitrate and nitrite ions on a copper electrode in aqueous potassium chloride solutions was studied using cyclic voltammetry technique. The cyclic voltammograms showed that nitrate and nitrite ion reduction occurred in the 0.14 M KCl solution with peak potentials of -1.25 to -1.30 V and -1.20 to -1.25 V (Ag/AgCl) respectively. It was suggested from the data analysis that in the potassium chloride solution the reduction of nitrate and nitrite ions is irreversible. A minimal effect of pH on the reduction rate of nitrate and nitrite ions was found for the acidic and neutral solutions, but it increased in the alkaline solutions